(untitled) (Texas Journal of Medical Science, 2022)
Genital herpes (GH) is one of the most socially significant problems in the clinical practice of dermatovenerologists, obstetricians, gynecologists, urologists. The number of patients with GH has increased by 30% over the past 10 years. The main role in the etiology of HSV belongs to HSV type 2 (HSV-2), but the pathogens of this pathology can become both HSV type 1 (HSV–1) and a combination of both types of herpes simplex virus. The prevalence of HSV-2 infection in the population ranges from 7 to 40% and averages 20%